Efficacy of seawater for the treatment of allergic rhinitis: a randomized clinical trial - María de la Luz Valencia Chávez; Wilmer Soler Terranova; Javier Rosique Gracia; Olga Morales Múnera (Social Medicine Publication Group, 2016)
Objective: To evaluate the efficacy of diluted seawater (SW) nasal lavage and ingestion in the treatment of symptoms of allergic rhinitis, including nasal discharge, in children (2-6 years) compared with physiological "normal" saline solution (NS) as a control. Methods: Controlled, triple-blind, randomized clinical trial of 164 children with allergic rhinitis, drawn from schools and health centers located in areas with low socioeconomic status. Children were divided into two treatment groups: SW and NS. Clinical variables were evaluated at the beginning of the trial and at weeks 2 and 12. At the beginning and the end of the study an anthropometric growth check was performed. Results: 16 of the 164 children left the study early. There were 83 subject in the SW arm and 81 in the NS arm. In weeks 2 and 12, both groups achieved significant reductions in rhinorrhea (p